ANALISIS FAKTOR PENYEBAB KESULITAN MEMBACA PERMULAAN PADA KELAS III SDN 4 METRO BARAT - Fauziana, Nada; Mega Diana, Siska; Nuraini, Siti; Destini, Frida (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The research problem addressed in this study is the difficulty of early reading among third-grade elementary school students, despite the expectation that, at this stage, learners should have achieved reading fluency as a foundational skill for comprehending instructional materials. This study aims to analyze the factors contributing to early reading difficulties among third-grade students at SDN 4 Metro Barat in the 2025/2026 academic year. This research employs a descriptive qualitative approach, with students serving as the primary informants, while teachers and the school principal act as supporting informants. Data collection techniques include observation, interviews, and documentation. The findings indicate that early reading difficulties are hierarchical and interrelated, encompassing both technical aspects and reading fluency. Out of 32 students, 9 were identified as experiencing difficulties in letter recognition, phonemic differentiation, syllable blending, reading simple sentences, and achieving reading fluency. These difficulties are influenced by internal factors, such as cognitive capacity, concentration, and self-confidence, as well as external factors, including family support and literacy habituation within the social environment. Keywords: Reading Difficulties, Early Reading, Students